THE ASSOCIATION BETWEEN KNOWLEDGE AND IRON TABLET CONSUMPTION AMONG PREGNANT WOMEN IN PONDOK KACANG, SOUTH TANGERANG CITY, INDONESIA - Siti Riptifah Tri Handari; Munaya Fauziah; Nirmala Harahap; Mohammad Ainul Maruf (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Based on 2013 Indonesian Basic Health Research (IBHR), anemia prevalence among pregnant women in Indonesia was still high. Some studies found that knowledge is one of the main factor which affects the consumption of iron tablet among pregnant women. The Pondok Kacang Timur Health Center (Puskesmas Pondok Kacang Timur) in South Tangerang City wasselected as our study site due to their coverage on iron tablet consumption was the lowest in the city. South Tangerang City itself is a new city or town located in the southern part of the Jakarta Capital City (DKI Jakarta). Aims: This study aimed to know the association between knowledge about iron tablet and iron tablet consumption among pregnant women in Pondok Kacang, South Tangerang City, Indonesia. Methods: This study was analytical descriptive research with cross-sectional method. It was conducted from 25 July to 20 August 2016. The sample size was calculated using Lemeshow formula so it was obtained a total of 120 formerly pregnant women who currently have infant age of 0 to 6 years old as participants. The data collection was done through interviews using aquestionnaire. Results: The study revealed that only 34.2% of respondents took iron tablet as given by health worker during their pregnancy. Mean score of knowledge was 7.8 of 13 questions. It was found that there was a correlation between knowledge and iron tablet consumption. Conclusion: The study suggests to improve knowledge of pregnant women in order to increase their compliance on iron tablet consumption.